Real-Time Static Image Classification Algorithms - Gen, Wenqing (Харківський національний автомобільно-дорожній університет, 2024)
The object of research is the algorithm for classifying text collections. The purpose of the work is to develop a web service for classifying text messages using a neural network approach. As a result of the work, the subject area was analyzed, the task was set and a web service was designed for classifying emails according to the given vacancies.
Keywords: web service; classification; word2vec; neural network; ms sql server; asp.net; web api; react; tensorflow